Rereading qahal as Deuteronomist history works: Literal and ideological criticism approach - Napitupulu, Pieter Anggiat; Santoso, Agus; Putrawan, Bobby Kurnia (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
Some biblical scholars understand Deuteronomy to be the end of the Pentateuch. Before the nation of Israel became a confederate system, the socio-political reality could usually be seen in the composition, interaction, and behavior of relationships in society, which were assumed to be political elements. The Israeli confederation which is like the ambition centered on Yahweh is what the author refers to as Israel's "Qahal". Martin Noth explains Qahal Israel in Deuteronomist Historical Works, which began with a period of wandering under the leadership of Musa, then became an immigrant in the Land of Canaan, followed by Saul's leadership where Israel asked the king to directly lead the Israelites. In the leadership of David and Solomon, which originally had 12 tribes, eventually split into two nations. With this monarchical system, God hates, because he does not reject God as the government in their life. The purpose of this study was to find the location of the Deuteronomy and Eating Qahal books in the book of laws. The research method uses critical research with a study of literature and ideological sources using Martin Noth's theory which is an early thesis in Deuteronomic History Works. The novelty of this research is the existence of a new meaning where the main message of Deuteronomic history works, namely Israel is forced to turn to God, confess His sins, and return to submit and obey His word because they have been chosen to be God's people (2 Ki 17:13).